1989
DOI: 10.1111/j.1600-0714.1989.tb00723.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric study of pseudoepitheliomatous hyperplasia in granular cell tumors of the tongue

Abstract: Several reports have mentioned the possibility of misdiagnosing pseudoepitheliomatous hyperplasia (PEH) of the overlying mucosa of a granular cell tumor as a squamous cell carcinoma (SCC). Because of this, morphometry was applied to five granular cell tumors with PEH and five well-differentiated SCC of the tongue. In addition, ten normal tongues have been examined. The mean area, the mean perimeter and the mean diameter of the 50 largest squamous epithelial nuclei in 50 fields were found to be significantly la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 5 publications
2
4
0
Order By: Relevance
“…On the whole, among the quantitative morphometric parameters of the nuclei analyzed in this study, nuclear area and nuclear perimeter were significantly larger in pN-positive cases than in pN-negative cases, while the nuclear circular rate was lower in pN-positive cases but not significantly so. These results suggest that malignant nuclei become aspherical, which would be consistent with previous reports [8] , [35] – [42] . Regarding the patient’s age, however, it has been reported that low age (<42 years) was associated with the development of cervical lymph node metastasis within a short time frame (≤50 days) [45] .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…On the whole, among the quantitative morphometric parameters of the nuclei analyzed in this study, nuclear area and nuclear perimeter were significantly larger in pN-positive cases than in pN-negative cases, while the nuclear circular rate was lower in pN-positive cases but not significantly so. These results suggest that malignant nuclei become aspherical, which would be consistent with previous reports [8] , [35] – [42] . Regarding the patient’s age, however, it has been reported that low age (<42 years) was associated with the development of cervical lymph node metastasis within a short time frame (≤50 days) [45] .…”
Section: Discussionsupporting
confidence: 93%
“…Size and contour irregularities of the nuclei are important features in the grading of OSCC [35] – [40] . Furthermore, it was reported that the nuclear size was larger in proportion to the grade of malignancy [41] , [42] .…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, computerized image analysis of nuclear morphometric features like area, minimum diameter, and perimeter showed an increase in histological sections of OSCC as compared to normal buccal mucosa (control) in concordance with the study by van der Wal et al and Kinoshita et al [ 9 , 15 ].…”
Section: Discussionsupporting
confidence: 92%
“…Nuclei of epithelial tumor cells with well demarcated, clean, and nonoverlapping borders with absence of pyknosis were selected. The selected nuclei were assessed for the following features: nuclear diameter (in microns), nuclear area (in square microns), nuclear perimeter (in microns), and shape description (circularity graded on scale of 0 {a line}-1 {a circle}) [ 9 ].…”
Section: Methodsmentioning
confidence: 99%
“…[1213] NF was found to be less in carcinoma groups than normal mucosa, suggesting that irregular or elliptical nuclei predominate in the carcinoma groups. Though NF reduced as grades of carcinoma increased, the difference was not statistically significant between carcinoma groups 2 and 3.…”
Section: Discussionmentioning
confidence: 98%